Pluralisme dan Integrasi Sosial: Analisis Sosiokultural Tentang Ma’kombongan Kalua’ Dalam Masyarakat Toraja Sebagai Model Integrasi Sosial Dalam Konteks Masyarakat Plural - HANS LURA; AGUSTINUS KARURUKAN SAMPEASANG (KINAA: Jurnal Teologi, 2018)
Plural society is a social fact, it is a necessity that cannot be avoided. Meaning that human entities are diverse such as ethnicity, religion, race, class, culture and so on but plurality actually makes human life beautiful and dynamic like a rainbow. With the existence of color variants in an integrative spirit that gives extraordinary beauty, comfort, admiration and inspiration. Each color is not mutually negating, but the nature of each color remains and contributes to an integrative rainbow color circuit system. Plural society life like rainbow. Each tribal, religious, racial and class entity must be respected and appreciated for its existence no matter how small the entity must be respected and valued in the spirit of social integrity. This model of social integrity that provides comfort, beauty and harmony for every existing social entity.The pluralist social integrity model must be able to be managed fairly and well so that the existing conflict can be managed constructively and dynamically for the progress of civilization in society. This integrity model can be realized if there is a spirit of recognition, acceptance, and respect so that all social entities must contribute to the movement of reconciliation, cooperation, tolerance and respect for others. in order to realize this purpose, the Writer conduct research on culture of “Ma’kombongan kalua” in the Toraja society.